316 EVICTION Study: Preliminary results in solid tumor patients with ICT01, a first-in-class, gamma9 delta2 T cell activating antibody targeting butyrophilin-3A. (10th December 2020) - Marabelle, Aurelien; Jungels, Christiane; Bono, Johann De; Vey, Norbert; Wermke, Martin; Garralda, Elena; Gassart, Aude de; Brune, Patrick; Valentin, Emmanuel; Iché, Marina; Olive, Daniel; Frohna, Paul
Abstract : Background: Gamma9 Delta2 (γ9δ2) T cells are an important component of the innate anti-tumor immune response whose infiltration into solid tumors has been associated with a positive prognosis, making γ9δ2 T cells an attractive target for the next generation of cancer immunotherapy. Butyrophilins (BTNs) are a family of immune checkpoint molecules that regulate γ9δ2 T cell activity, including BTN3A that is a potent endogenous activator of γ9δ2 T cells following phosphoantigen (pAg) binding to the intracellular domain of BTN3A1. This observation led to the design and development of ICT01, a humanized, monoclonal antibody that binds all 3 isoforms of BTN3A1/A2/A3 and induces pAg-independent γ9δ2 T cell activation, for the treatment of patients with solid or hematologic tumors. Methods: EVICTION (www. clinicaltrials.gov NCT04243499 ; EudraCT Number: 2019-003847-31) is a first-in-human, two-part, open-label, clinical study to assess the safety, tolerability and activity of intravenous doses of ICT01 as monotherapy and in combination with pembrolizumab, in patients with advanced-stage, relapsed/refractory cancer. Following Competent Authority and Ethics Committee approvals, the study is being conducted at cancer centers in France, Belgium, Spain, Germany, and the UK. Patients provide signed informed consent prior to screening. Eligible patients receive ICT01 (Range: 20 µg to 200 mg) every 3 weeks with blood samples collected at multiple timepoints for immunophenotyping and cytokine analysis (IFNγ, IL-1β, IL-2, IL-4, IL-6, IL-8, IL-13, TNFα). Tumor biopsies are collected at baseline and Day 28 and stained by immunohistochemistry for BTN3A, γ9δ2 T cells and other markers of anti-tumor immunity. Results: Cohort 1 comprising 6 patients with solid tumors (3 Colorectal, 1 Pancreatic, 1 Ovarian, 1 Melanoma) has been enrolled and treated with ICT01 doses ranging from 20 to 700 µg. No dose-limiting toxicities or related SAEs have been reported. Target occupancy on T cells at 4 hours post first dose was 10% at 70 µg (n=1), 31% at 200 µg (n=2) and 34% at 700 µg (n=2), which was reflected at 24 hours post dose by a 73%, 91% and 97% decrease from baseline in the number of circulating γ9δ2 T cells, respectively. On Day 7, γ9δ2 T cells remained decreased by 37%, 75% and 76%, respectively. There were no effects on CD4 or CD8 T cells, NK cells, or B cells. Transient increases in IFNγ, secreted by activated γ9δ2 T cells, were observed in 4/6 patients. No cytokine release syndrome was observed. Data from the paired tumor biopsies are still being generated and will be presented. Conclusions: The preliminary results demonstrate that ICT01 has the potential to safely activate the innate anti-tumor potential of γ9δ2 T cells through BTN3A. Acknowledgements: . Trial Registration: www.clinicaltrials.gov NCT04243499 ; EudraCT Number: 2019-003847-31 Ethics Approval: This study was approved by the following Ethics Committees: COMITE DE PROTECTION DES PERSONNES, Sud-Méditerranée V (Gustave Roussy, IPC), Comité d'Ethique Institut Jules Bordet, COMITÉ DE ÉTICA DE INVESTIGACIÓN CLÍNICA CON MEDICAMENTOS del Hospital Universitari Vall d'Hebron, Ethikkommission an der TU Dresden, HRA London-Surrey Borders Research Ethics Committee. Consent: Written informed consent was obtained from the patient for publication of this abstract and any accompanying images. A copy of the written consent is available for review by the Editor of this journal.